Tourist Loyalty to Halal Tourism in Indonesia: The Role of Services Quality, Satisfaction, and Experience Quality - Rahayu, Sri; Candera, Mister (Jurnal Manajemen Bisnis, 2023)
Research aims: This study aims to develop an original model of halal tourism by considering the service quality variable and its effect on tourist loyalty with satisfaction as a mediator variable and experience quality consisting of halal food, halal facilities and services, and people at the destination as moderator variables.Design/Methodology/Approach: This study adopts an empirical approach. Data were collected using questionnaire distributed to respondents that were selected through purposive sampling based on their previous visits to halal destinations in Indonesia. A total of 440 questionnaire responses were subjected to quantitative analysis using the Structural Equation Modeling.Research findings: Our study findings indicated that services quality was one of the factors with positive, significant impacts (direct and indirect) on tourist loyalty. In addition, experience quality seemed to strengthen this impact.Theoretical Contribution/Originality: This research offered a novel insight that that the satisfaction and loyalty of tourists visiting halal tourism can be increased through improving experience quality.Practitioners/Policy Implications: This research is expected to be a reference and consideration for halal tourism business actors in their efforts to increase visitor satisfaction where major coniderations should be put on halal accommodation and halal services. Visitor experience is an important factor to increase the number of visitors to halal tourism.Research Limitations/Implications: The large sample size relatively complicated the timely data collection.